(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
There were many methods of linguistic use in the Holy Quran, with a variety of rhetorical and expressive purposes. Some of these methods require careful consideration, and the precise contemplation of the relationships that form the divine meaning and purposes in different levels (verbal relations, semantic relationships, rhythmic, contextual, and other).Anaclothe style one of those methods that establishes rich relationships at all textual levels, and this method has a strong and influential presence in the holy Quran, because it converts the transmission of language formats ( speak, the speech, absent), and change them in accordance with the requirements of the situation, and the rhetorical purposes behind them, it thus removes the linguistic text from the stereotypical dialogue, and breaks the expectations horizon of the receiver – direct and indirect- each according to its location from the message contained in that text The search will stand on the anacoluthe style in SuratYunus, trying to monitor stylistic variations, and the dialogue in the linguistic text in the Surat, it effects of it in the clarification of rhetorical purposes and divine purposes, and communicating it to the recipient in an expressive way that controls thought, and draw attention to the contemplation of linguistic aberrations, and the new textual relations resulting from this deviation or the so-called exit in the appropriate apparent.